INDULA Initiative: Advancing Sustainable Development in Mekarwangi Village, Tangerang - Oktaviani, Retno Fuji; Ekawanti, Wahyumi; Rahayu, Sri; Anwar, Syaiful (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
The INDULA (Inovasi Daur Ulang Sampah/Waste Recycling Innovation) program for sustainable development in Mekarwangi Village was initiated to address the growing volume of waste and the community’s limited knowledge of waste management. These challenges negatively impacted the environment and public health, necessitating efforts to educate residents on the importance of recycling. The program employed a structured methodology encompassing preparation, implementation, and evaluation stages. Participants were selected using purposive sampling, focusing on individuals directly affected by the waste management issues. Data collection utilized pre-test and post-test instruments to assess program impact. The analysis revealed significant changes before and after program implementation. Initially, 75% of household waste in the village underwent no sorting, and only 20% of respondents had basic knowledge of recycling. The community also lacked recycling skills and access to markets for recycled products. Following the program, at least 80% of participants understood the importance of recycling and its practical applications. Housewives and youth began creating innovative products from waste, with 50 individuals trained to produce items of economic value. Recycled products were introduced to local markets and e-commerce platforms, leading to a 20% increase in local economic income within three months of training. Additionally, the village established a more structured waste management system, reducing landfill waste by up to 50%. This program demonstrated a measurable positive impact on community awareness, skill development, and local economic growth.